Chlorine-doped α-Co(OH)2 hollow nano-dodecahedrons prepared by a ZIF-67 self-sacrificing template route and enhanced OER catalytic activity. Issue 32 (22nd July 2019) - Zha, Qingqing; Xu, Wenyan; Li, Xiaolei; Ni, Yonghong
Abstract : A ZIF-67-self-sacrificing template strategy was designed for the synthesis of undoped/Cl-doped α-Co(OH)2 hollow nano-dodecahedrons with enhanced OER performance. Abstract : Hollow α-Co(OH)2 and Cl-doped α-Co(OH)2 nano-dodecahedrons were successfully synthesized via a ZIF-67-assisted template route in the absence/presence of NaCl. The reactions were carried out in a Teflon-lined stainless-steel autoclave at 40 °C for 4 h, employing dodecahedral ZIF-67 and hexamethylenetetramine (HMT) as the reactants. The as-obtained hollow nano-dodecahedrons were characterized by X-ray powder diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), Fourier transform infrared (FTIR), X-ray photoelectron energy, EDS mapping and N2 sorption–desorption technologies. Electrochemical measurements showed that both α-Co(OH)2 and Cl-doped α-Co(OH)2 hollow nano-dodecahedrons displayed excellent catalytic activities for the oxygen evolution reaction (OER) and Cl-doped α-Co(OH)2 hollow ones possessed stronger electrocatalytic performances. To deliver a current density of 10 mA cm −2, Cl-doped α-Co(OH)2 hollow nano-dodecahedrons required a low overpotential of 298 mV, which is smaller than most reported α-Co(OH)2 catalysts. Also, the as-obtained hollow catalyst still had excellent OER cycling stability and durability. After 1000 CV cycles, the overpotential merely slightly increased. Continuously catalyzing at the current density of 10 mA cm −2 for 40 h, the voltage only increased ∼2.5%.